Assessment of bacterial and parasitic contamination of fruits gathered from specific local markets in Addis Ababa, Ethiopia - Demisie, Kelelaw Nigusie; Melese, Daniel Molla (Frontiers in Sustainable Food Systems, 2024)
Background Around the world, food-borne illnesses are still a frequent and significant hazard to public health. Human infection outbreaks brought on by eating raw fruits have happened more frequently. Fruits have been connected in recent years to a number of outbreaks of food-borne illness around the globe, including in Ethiopia. Objective To assess bacterial and parasitic contamination of fruits gathered from specific local markets in Addis Ababa, Ethiopia. Methods A cross-sectional study was carried out using fruits gathered from Addis Ababa local marketplaces. Convenient sampling were applied. With the assumption that each vendor provided 30 samples, a total of 120 fruit samples were gathered. Fruit samples were gathered in a plastic bag that had been sanitized and then brought to the lab for bacterial and parasitological investigation. All of the samples were checked for intestinal parasites and bacterial contamination. SPSS software version 25 was used to analyze the data. The Pearson's Chi-square test was used to assess categorical variables. The student's t-test was utilized to compare continuous variables, which were represented as the mean ± standard deviation. Using both univariate and multivariate analysis, odds ratios (OR) with 95% confidence intervals (CI) were computed. Statistical significance was defined as a P < 0.05. Results There was a 100 (83.3%) level of bacterial contamination. While Salmonella and Shigella species were not recovered, S. aureus isolates 16 (13.3%) were the most common bacterial contamination, followed by E. coli isolates 8 (6.7%). The samples of bananas, mangos, papayas, and avocados from all four sites had total coliform (TCC) bacteria ranging from 2.1 × 103 to 3.2 × 104, 8.3x 102 to 1.8x 105CFU/g, 1.6x 102 to 3.7 x 104, and 1.2x 102 to 3.8 x 104 CFU/g, in that order. No parasites were found in this investigation. Conclusion and recommendation It is usually recommended that customers in this research region wash and handle infected fruits properly to prevent bacterial illnesses. In addition, fruit dealers should have their bacterial contaminations routinely inspected. Large-scale research is advised to support this discovery.